Puppet As Media In Improving Young Learners’ Participation In Conversation - Wardah, Wardah; Nabillha, Ridha (Jurnal Visi Ilmu Pendidikan, 2015)
This action research aimed to improve students’ participation in English conversation. The participants were 38 of the fifth grade students of SD Muhammadiyah 2 Pontianak. Observation and fieldnote were used to collect and analyze the data.  The research findings  showed that the use of puppet as media can improve students’ participation in English conversation. In the first cycle, the percentage of the students’ participation in English conversation was 53%: 11 students participated in asking question, 6 students participated in answering questions,  and 3 students participated in giving opinions. In the second cycle, the students’ participation improved to 61%: 14 students participated in asking question, 8 students participated in answering question,  and 4 students participated in giving opinions. Finally, in the third cycle, the percentage of students’ participation was 74%: 14 students participated in asking questions, 11 students participated in answering questions,  and 5 students participated in giving opinions. Cycle two and three  showed improvement on the students’ participation in asking questions, answering questions, and giving opinions when being taught by using puppet. Hence, Puppet as media can improve students’ participation in English conversation. Keywords: Puppet, Young Learners, Conversation